THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ROMANIA’S ECONOMY: SECTORAL IMPACTS, LABOR MARKET SHIFTS, AND FUTURE FORECASTS - Davide Nicola PÂNTEA; Oana Ruxandra BODE; Rozalia Veronica RUS; Valeria GIDIU (Studia Universitatis Babeş-Bolyai Negotia)
Modern technologies are continuously transforming the world, and Artificial Intelligence may be considered one of the most important discoveries of this century. The unknown nature of this technology, mixed with the rational and irrational fears of the vast majority, makes this research a must to give some order to the chaos created in the last few years. A concise and explicative explanation of Artificial Intelligence (AI) is given to understand the potential of this technology. Many workers perceive this technology as a threat, while their employers see it as an opportunity to cut costs. The main objective of this study is to identify the possible impact that the application of AI may have in the future, in Romania, in each economic sector (primary, secondary, and tertiary). This will lead to an in-depth analysis of the transition that AI will force on these sectors.